#TITLE_ALTERNATIVE# - AJI NUGRAHA (NIM : 255 13 013), BINA
According to ASELI (Asosiasi Energi Laut Indonesia) Research in 2014, Larantuka strait is a potential site of tidal current energy. Therefore, it needs energy analysis of electricity power potential. It is analysed from current speed as the result of hydrodynamic simulation using Mike 3 Flow Model FM. The model is calibrated by comparing the result values of water level and 3 spot of current speed survey (LKA1, LKA2, and LKA3). The calibration error values are 5.51%; 9.07%; 19.17% and 20.82% respectively. The maximum technical resources energy potential, produced from the current turbine, is 247.6 MWh during 2014. The current turbine efficiency is 0.55 and its cut in speed is 0.5 meter/second. It is an horizontal axis turbine with 10 meter blade diameter. Its total weight is 941 tonne. Beside energy analysis, this research also analyse the turbine structure includes inplace analysis and stability foundation analysis. The structural analysis refers to code criteria of API RP2A-WSD. The results of stability foundation analysis are safety factor values. They are 1.51 ; 18.1 ; and 84.7 respectively for safety factor values of sliding, overturning moment, and bearing capacity failure.